Negotiating cultural rights : issues at stake, challenges and recommendations - Belder, Lucky; Porsdam, Helle, 1956- (Edward Elgar Publishing, 2017)
The various reports on cultural rights by UN Special Rapporteur Faridah Shaheed have provided a new universal standard for topics ranging from cultural diversity, cultural heritage, the right to artistic freedom and the effects of today's intellectual property regimes. This book's team of international contributors reflects upon the many aspects of cultural rights discussed in Faridah Shaheed's reports and discusses how cultural rights support cultural diversity, foster intercultural dialogue and contribute to inclusive social, economic and political development. Drawing from a range of disciplines, the contributing authors explore the meaning and position of cultural rights and the implications these may have for international relations, the international legal order and cross-cultural understanding, while also offering recommendations for the future. Key topics discussed include the link between culture and science, gender and human rights, rights to artistic freedom, the importance of historical narratives and the impact of advertising and marketing on the enjoyment of cultural rights. This worthwhile contribution to the current cultural rights debate will be of interest to academics and students teaching and studying in the fields of culture, heritage and human rights as well as policymakers who are working within cultural rights related issues.